2008
DOI: 10.1017/s0022112008000487
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of non-ideal plumes with sudden reductions in buoyancy flux

Abstract: We model the behaviour of isolated sources of finite radius and volume flux which experience a sudden drop in buoyancy flux, generalizing the previous theory presented in Scase et al. (J. Fluid Mech., vol. 563, 2006, p. 443). In particular, we consider the problem of the source of an established plume suddenly increasing in area to provide a much wider plume source. Our calculations predict that, while our model remains applicable, the plume never fully pinches off into individual rising thermals.We report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…However, consistent with our interpretation of figure 2, the change in plume width is not readily discernible from the radial extent of the passive scalar field presented in figures 3 and 4 of Scase et al (2008). Only by quantifying the width of the plume with a top-hat width based on the concentration of the passive scalar do Scase et al (2008) find that the plume becomes narrower (figure 6 of their study). The interpretation and observed behaviour of the plume radius will be discussed in further detail below.…”
Section: Unsteady Plumessupporting
confidence: 66%
See 2 more Smart Citations
“…However, consistent with our interpretation of figure 2, the change in plume width is not readily discernible from the radial extent of the passive scalar field presented in figures 3 and 4 of Scase et al (2008). Only by quantifying the width of the plume with a top-hat width based on the concentration of the passive scalar do Scase et al (2008) find that the plume becomes narrower (figure 6 of their study). The interpretation and observed behaviour of the plume radius will be discussed in further detail below.…”
Section: Unsteady Plumessupporting
confidence: 66%
“…Looking at the buoyancy field and the boundary of the plume in figure 2, one does not get the impression that the width or radial extent of the plume is strongly affected by the step change in the buoyancy flux. In this regard, we note that experimental observations of a plume, whose source buoyancy flux was suddenly reduced at the source, suggested that such plumes become narrower in the vicinity of the step change (Scase et al 2008). However, consistent with our interpretation of figure 2, the change in plume width is not readily discernible from the radial extent of the passive scalar field presented in figures 3 and 4 of Scase et al (2008).…”
Section: Unsteady Plumessupporting
confidence: 64%
See 1 more Smart Citation
“…A contribution to experimental data pertaining to unsteady plumes was made by Scase, Caulfield & Dalziel (2008), who investigated the effects of a sudden reduction in buoyancy flux. In particular, Scase et al (2008) found that source conditions 502 J.…”
mentioning
confidence: 99%
“…Validation of the various self-similarity-based statistically unsteady turbulent jet and plume models in Scase, Caulfield & Dalziel (2008), Musculus (2009), Scase, Aspden & Caulfield (2009) and Craske & van Reeuwijk (2015b) indicates that assumption of self-similar mean axial velocity profiles provides a useful basis for development of models in statistically unsteady jets; however, the underlying assumption that self-similarity persists as the jet decelerates has not been examined directly. On the contrary, the measurements by Borée et al (1996) indicate that the radial profiles of phase-averaged axial velocity and other velocity moments deviate from the self-similar profiles of a statistically steady jet as the jet decelerates, and that the profiles vary axially through the confined deceleration region (Borée et al 1996(Borée et al , 1997.…”
Section: Introductionmentioning
confidence: 99%